Položaj gorskih bukovih gozdov v Sloveniji - Košir, Živko (Gozdarski vestnik, 2007)
The article compares vegetation composition of mountain beech forests stand ofthe central Slovenia to the similar communities in Croatia and southern Central Europe. On the basis of vegetation and habitat conditions and beech communities' similarities we critically deal with their naming and previous nomenclature revisions. We present a detailed analysis of mountain beech vegetation units on the basis of vegetation structure and habitat conditions. The comparison has shown that some communities in this space need to be named anew or renamed to ensure indisputable determination of mountain beech syntaxa. In the last chapter, some characteristics of the researched beech communities, important for managing their phytocoenoses, are listed.
Keywords: bukovi gozdovi; rastlinske združbe; Slovenia; Slovenija